2020
DOI: 10.1017/jfm.2020.562
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics of premixed flames: from deterministic stages to stochastic influence

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 88 publications
(211 reference statements)
1
11
0
Order By: Relevance
“…As can be seen, the differences between the fit obtained here (red line) and the one obtained in [27] on the same data but with the standard dispersion relation (black line) are small. In particular, the dispersion relation is slightly shifted towards the large wavenumbers and a new cutoff wavenumber is introduced on the left side of the dispersion relation.…”
Section: B Comparison With Experimentsmentioning
confidence: 50%
See 4 more Smart Citations
“…As can be seen, the differences between the fit obtained here (red line) and the one obtained in [27] on the same data but with the standard dispersion relation (black line) are small. In particular, the dispersion relation is slightly shifted towards the large wavenumbers and a new cutoff wavenumber is introduced on the left side of the dispersion relation.…”
Section: B Comparison With Experimentsmentioning
confidence: 50%
“…The dynamics described by MS equation was even succesfully compared to DNS results [18] and experiments [25,26] on a quantitative level for moderate time of propagation (≈ 10 × 1/σ M ). At larger time, we have argued in a recent study that the background noise and sensitivity to initial conditions play an important role in the observed dynamics, therefore limiting a face to face comparison between experiments and numerical simulations [27]. However, we have suggested that the MS equation could still be relevant in predicting some statistical features of the flame front topology.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations